Enabling Technology for Supramolecular Chemistry - Ollerton, Katie; Greenaway, Rebecca L.; Slater, Anna G. (Frontiers in Chemistry, 2021)
Supramolecular materials–materials that exploit non-covalent interactions–are increasing in structural complexity, selectivity, function, stability, and scalability, but their use in applications has been comparatively limited. In this Minireview, we summarize the opportunities presented by enabling technology–flow chemistry, high-throughput screening, and automation–to wield greater control over the processes in supramolecular chemistry and accelerate the discovery and use of self-assembled systems. Finally, we give an outlook for how these tools could transform the future of the field.